2019
DOI: 10.3390/app9020233
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive Structural Modeling and MICMAC Analysis for Identifying and Benchmarking Significant Factors of Seismic Soil Liquefaction

Abstract: Seismic soil liquefaction is considered as one of the most complex geotechnical earthquake engineering problems owing to the uncertainty and complexity involved in soil parameters, seismic parameters, and site condition factors. Each one of these parameters contains a variety of factors that trigger liquefaction and have varying degrees of importance. However, estimating accurate and reliable liquefaction-induced hazards requires identification and benchmarking of the most influential factors that control soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 37 publications
0
45
0
1
Order By: Relevance
“…Post this visit, eight experts, two from each organization, holding the position of an assistant manager and above, along with two experts from academia who come from the operations and supply chain background, were approached for their valuable inputs. The number of expert opinions was determined judiciously in the light of previous studies, which were similar and engaged three to fifteen experts for such purposes [ 27 , 35 , 83 , 84 ]. These experts were briefed about the subject of inquiry before being interviewed, using a semi-structured questionnaire.…”
Section: Objective and Methodologymentioning
confidence: 99%
“…Post this visit, eight experts, two from each organization, holding the position of an assistant manager and above, along with two experts from academia who come from the operations and supply chain background, were approached for their valuable inputs. The number of expert opinions was determined judiciously in the light of previous studies, which were similar and engaged three to fifteen experts for such purposes [ 27 , 35 , 83 , 84 ]. These experts were briefed about the subject of inquiry before being interviewed, using a semi-structured questionnaire.…”
Section: Objective and Methodologymentioning
confidence: 99%
“…The steps of the interpretive structural modeling method [33,34] that have been performed in the present study are as follows:…”
Section: Research Methodsologymentioning
confidence: 99%
“…For instance, 105 data samples were measured in the range of 2-4 with regard to the Ds parameter. (Ahmad et al 2019a;Ahmad et al 2019b;Hu et al 2015;Zhang 1998) showed detail understanding about the variables' selection and discretization. BBN has a good capability to deal with discrete variables, but is weak in continuous variables processing, so the nine significant factors and output (liquefaction potential, F10) require to be transformed into discrete values before the propose model is constructed accordance to the possible factor range and expert knowledge, as shown in Table 2.…”
Section: Data Set and Predictor Variablesmentioning
confidence: 99%